First, let's rewrite the expression for \( y \):
\[ y = -3x + 12x + 15 \]
Combine like terms:
\[ y = (12x - 3x) + 15 \] \[ y = 9x + 15 \]
Now, we want to find the zeros of the function, which means we set \( y = 0 \):
\[ 0 = 9x + 15 \]
To solve for \( x \), we can isolate \( x \) by first subtracting 15 from both sides:
\[ -15 = 9x \]
Next, divide both sides by 9:
\[ x = -\frac{15}{9} \]
Now, simplify the fraction:
\[ x = -\frac{5}{3} \]
Thus, the zero of the function \( y = -3x + 12x + 15 \) is:
\[ \boxed{-\frac{5}{3}} \]